CELEBRATING SHARIA INDONESIA: ISLAMIC HARMONY AND PANCASILA IN THE VISION OF INDONESIAN NATIONALITY - Lufaefi Lufaefi (Jurnal Ilmiah Al-Syir'ah, 2019)
This article discusses and offers at the same time the issue of formalizing Islamic law in Indonesia. It started with a debate about the ideals of the formalization of Islamic law, which never ended. The debate about this has led to at least two significant views, namely fundamentalism and secularism. The first group believes that Islam is a religion that prepares solutions to all problems. In the context of Indonesians, such rules override local state laws, such as the 1945 Constitution and the Pancasila ideology. Meanwhile, the second group tried to give up religion in answering modern problems. This article uses a qualitative method, and two knives of analysis, namely socio-historical and maqāṣid of the Koran. This paper proves that the ideology of the State of Indonesia, namely Pancasila, contains substantive sharia values. The values of Islamic law are contained in every principle and are following the vision of Indonesian nationhood as a nation that harmonizes between Islam and nationality. These values are relevant to the values that exist in the country of Medina as the first country formed by the Prophet Muhammad. With the values of Islamic law in the Pancasila, Indonesia is worth mentioning as a sharia country.